1997
DOI: 10.3406/arsci.1997.949
|View full text |Cite
|
Sign up to set email alerts
|

L'atelier de verrier de Lyon, du Ier siècle apr. J.-C, et l'origine des verres « romains »

Abstract: On présente les résultats des analyses effectuées sur le matériel de râtelier secondaire de verrier de Lyon, du milieu du 1er siècle de notre ère. Après quelques remarques sur les colorants et les décolorants des verres importés par l'atelier pour la fabrication de produits finis, on souligne la très grande homogénéité des compositions de ces verres, et on montre que c'est une caractéristique que possèdent en Occident tous les verres d'époque romaine dont on étudie les analyses. On montre que cette homogénéité… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 0 publications
2
64
0
1
Order By: Relevance
“…The tank furnaces of Israel were extremely large producing c. 8-9 tonnes of glass per firing (Freestone et al, 2000;Gorin-Rosen, 2000), but little further archaeological evidence of primary glass production in the 1 st -5 th centuries has yet been found (Paynter, 2006). Although, it has been suggested that further earlier sites may exist in Syro-Palestine and Egypt (Foy et al, 2003;Nenna, 2003;Nenna et al, 2000Nenna et al, , 1997. The furnace locations that have been found are located either near the favoured sand sources, such as the mouth of the Belus River, or close to the alkali sources, such as the Wadi Natrun, Egypt (Freestone et al, 2000;Nenna et al, 2000).…”
Section: The Archaeological Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The tank furnaces of Israel were extremely large producing c. 8-9 tonnes of glass per firing (Freestone et al, 2000;Gorin-Rosen, 2000), but little further archaeological evidence of primary glass production in the 1 st -5 th centuries has yet been found (Paynter, 2006). Although, it has been suggested that further earlier sites may exist in Syro-Palestine and Egypt (Foy et al, 2003;Nenna, 2003;Nenna et al, 2000Nenna et al, , 1997. The furnace locations that have been found are located either near the favoured sand sources, such as the mouth of the Belus River, or close to the alkali sources, such as the Wadi Natrun, Egypt (Freestone et al, 2000;Nenna et al, 2000).…”
Section: The Archaeological Evidencementioning
confidence: 99%
“…The calculated compositions of the hypothetical glasses were compared to the composition of Roman natron glass. Several different glass groups have been identified, such as Levantine 1, Levantine 2, Egypt 1, Egypt 2 and HIMT (Nenna et al, 1997;Freestone et al, 2000Freestone et al, , 2002bFreestone et al, , 2005Foy et al, 2003;Freestone, 2006). For comparison, we used the average values given by Foster and Jackson (2009) for first to fourth century natron glass from the eastern and western part of the Roman Empire.…”
Section: The Sand Survey and Analysismentioning
confidence: 99%
“…During the recent excavations of the harbour area of Classe, a large amount of glass was recovered and evidence of glass working was identified [1,2]. Although the archaeological study of the glass allows us to exclude primary production in the area under investigation and seems to support the centralised production model, in which raw glass is produced in a few primary production location and then exported to secondary workshops for vessel shaping [3][4][5], the present study, combining archaeological and archaeometric data, aims to answer various questions still open. These are mainly related to: 1) identification of the main glass compositions worked in Classe and their contextualisation in LateAntique groups, reported in the literature until now; 2) identification of provenance of raw glass worked in Classe, and, consequently, of the glass commercial routes; 3) extent, if any, of practice of recycling glass cullet, as an alternative to the import of fresh raw glass; 4) identification of eventual correlations between archaeological types and glass chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…To supply sites with tank furnaces where large-scale glass production occurred, such as those recently excavated at Jalame (Gorin-Rosen, personal communication), would require at least a tonne of natron for every tonne of glass produced and implies a high level of organisation and well-developed infrastructure. The Roman 'presence' in both Egypt and along the eastern Mediterranean would have facilitated this movement of bulk materials, as it would have the movement of the finished glass, by both sea and land routes (Nenna et al 1997). Pliny describes Egyptian natron being exported by sea (NH XXXVI,191), although for what purpose is not stated, in sun-dried, pitch-lined vessels, presumably because natron is easily soluble in water (NH XXXI, 114); another type of natron, from Lydia, was exported as tablets.…”
Section: Implications For Roman Glassmaking Organisation and Tradementioning
confidence: 99%
“…More intense competition for the natron might also be expected at times of increased demand for glass, which could be reflected in glass compositions particularly for glasses made outside Egypt; this observation might be supported by the lower ratios of soda to silica and lime, which are consistently found in glass types thought to originate in the Syrio-Palestinian region compared to varieties considered to be Egyptian (Foy et al 2003, Nenna et al 1997, Silvestri et al 2008. Interestingly Pliny (NH XXXI, 114) also states that Egyptian natron was often adulterated with lime, which could be detected by tasting a sample; any additions of this kind would also affect the composition of glass made from exported Egyptian natron, reducing the soda content whilst increasing the lime.…”
Section: Implications For Roman Glassmaking Organisation and Tradementioning
confidence: 99%